The effects of cash on delivery, online customer review, and rating on Tiktok shop application towards customer loyalty - Ice Syahriya; Abdurrahman Faris Indriya Himawan (Institute of Computer Science (IOCS), 2022)
This study aims to analyze the effects of Cash on Delivery, Online Customer Review and Rating on TikTok Shop application towards customer loyalty (study on TikTok shop customers). This study used quantitative research with the number of respondents as many as 100 respondents. Sampling technique of purposive sampling data were collected through survey of 100 respondents/participants. The study used primary data obtained from the distribution of questionnaires online. The respondents were Indonesians who had purchased on the TikTok Shop application. Then, non-probability sampling was used for sampling. In this study, it was found that there is a positive influence between Cash on Delivery, Online Customer Reviews, and Rating on the customers. The results revealed that variables of Cash on Delivery (X1) had positive effect or increased the customer loyalty variable (Y) by 27,9 %, variable of Online customer reviews (x2) and Rating (X3) had positive effect or increased to the customer loyalty variable (Y) by 31,6 %. The conclusion of this study is that there is a positive and significant effect of Cash on Delivery on customer loyalty. In addition, there is a positive and significant effect of online customer review and rating on customer loyalty.